The challenge of Mediterranean sclerophyllous vegetation under climate change: From acclimation to adaptation - Bussotti, Filippo; Ferrini, Francesco; Pollastrini, Martina; Fini, Alessio (Environmental and Experimental Botany, 2014)
Forecasting models for climate change in southern Europe differ from those proposed for central and northern regions mainly with regard to precipitation. In fact, a strong reduction in average rainfall, mainly caused by decrease frequency of rainy events, is believe to occur in the Mediterranean basin in the forthcoming hundred years. Increased frequency of drought events will be paralleled and exacerbated by warming. Differently from areas where plant growth is limited by sub-optimal temperature (i.e. boreal and most temperate forests) and where warming has been reported to increase carbon assimilation and growth, plants growing in the Mediterranean basin are currently near their temperature optimum, and warming may contribute (e.g. with drought) to impair photosynthesis and depress growth and survival. Rising atmospheric CO2 has been found to increase growth, photosynthesis water use efficiency, and may partially alleviate the deleterious effects of warming and drought. However, in areas where severe and prolonged drought episodes occur, severe photoinhibition and metabolic limitation to photosynthesis may prevent Mediterranean sclerophylls to take advantage of higher atmospheric CO2, and may slow down recovery after the end of the dry season. The most sensitive forest types consist in tree species which are, in the Mediterranean basin, at the southernmost limit of their distribution range. In contrast, thermophilous trees are expected to have a greater diffusion both in southern and central Europe, as winter cold stress will be reduced by warming. Yet due to great variability of ecological features, the alleged substitution of tree species can follow a natural pattern from south to north and from low to high altitudes, without considering obstacles deriving from urbanization. For these reasons, research on the performance and ecologic plasticity of different genotypes, on species selection, and on planting and management techniques can have strategic importance for adaptive forest management.
Keywords: Drought stress; Global warming; Ozone; photosynthesis; UV radiation; Vegetation shift

Functional traits and adaptive capacity of European forests to climate change - Bussotti, Filippo; Pollastrini, Martina; Holland, Vera; Brüggemann, Wolfgang (Environmental and Experimental Botany, 2014)
Increasing temperatures and drought risks through climate change are expected to have several consequences for European forests. Adaptive strategies may include: (i) persistence of the current forest types, thanks to the acclimatization to local conditions and to phenotypic plasticity of the populations; (ii) evolution, or local adaptation, i.e., change in genotype (frequencies) within the same species due to environmental pressure. It is favored by large within population diversity and (when possible) gene flow among populations; (iii) migration and substitution of species; and (iv) extinction of populations with low ecological plasticity, especially at the edges of their distribution or in the case of isolated (relict) populations. Because of the economic and ecological relevance of forests, it is of fundamental importance to apply appropriate forest management to make forests able to cope with the new environmental conditions. This may include changes in the composition and structure of forest stands, selection of adapted provenances of the most important European tree species or, if this is regarded as insufficient, assisted migration (i.e., the use of species suitable for the future climatic conditions) and, alternatively, substitution of native with non native species. The intraspecific (genetic and phenotypic) variability at a given site has been proven to be often higher than the variability among sites. Species with a large distribution range are supposed to have a wide variety of genotypes, allowing them to be adapted to different environmental conditions. Genetic variability and phenotypic plasticity are the key factors for the identification of useful tree genotypes for future forestation programs. Adaptation to drought, i.e., the probably most important future abiotic risk factor for forestry, can be reflected in variation of key functional traits (FT), at morphological, physiological and phenological level. FT utilized to screen for adapted genotypes in common gardens and provenance trials include growth, survival, leaf flushing and senescence, foliar features as leaf mass per area and nitrogen content, water use efficiency (e.g., estimated by analysis of the stable carbon isotopes, d13C) chlorophyll content, photosystem II functioning, and photosynthetic capacity under water shortage. Current modeled simulation of future forest distribution suggests the expansion of forests at the highest latitudes and altitudes, alongside with a reduction in the hottest and driest Mediterranean regions of South Europe. The general expectations, however, may be disproved especially at a regional level, by factors unexpected or not well known, such as possible extreme climatic events and increased roles of parasites/diseases (with negative effects), or high capacity of forest persistence or adaptation (with positive effects). Natural migration and species substitution can be hampered by co-factors of climate change, such as forest fragmentation and increased frequency and intensity of forest fires.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Adaptation; Extinction; functional traits; Local evolution; migration; Phenotypic plasticity; Phenotyping; provenances

Holm oak (Quercus ilex L.) decline in coastal tuscany (central italy): first research in a permanent plot - Ferretti, Marco; Bussotti, Filippo; Cozzi, Alberto; Gellini, Romano (Annali di Botanica, 2013)

Ozone stress in woody plants assessed with chlorophyll a fluorescence. A critical reassessment of existing data - Bussotti, Filippo; Desotgiu, Rosanna; Cascio, Chiara; Pollastrini, Martina; Gravano, Elisabetta; Gerosa, Giacomo; Marzuoli, Riccardo; Nali, Cristina; Lorenzini, Giacomo; Salvatori, Elisabetta; Manes, Fausto; Schaub, Marcus; et al. (Environmental and Experimental Botany, 2011)
This paper proposes an overall reassessment of results from ﬂuorescence transient (FT) and modulated ﬂuorescence (MF) analysis on tree species subjected to treatment with ozone. Findings from literature and open-top chamber experiments were used in this review, in order to identify damage mechanisms and repair/avoidance strategies. Main results are summarised below. (i) The most widely used parameter to assess the response to ozone treatment was the quantum yield of primary photochemistry in the dark-adapted state (ϕPo, or FV/FM). This parameter proved to be very stable in stress and control conditions. Ozone-induced stress – and the related loss of photosynthetic efﬁciency and performance – was characterized by the change occurring in all parameters connected with the controlled dissipation: reduction of FM, FV/FM, RC/CS0 (in the ﬂuorescence transient analysis) and NPQ (in theMF analysis). This can be considered as a down-regulationmechanism aimed at lowering the electron supply as a consequence of a reduced demand from the Calvin cycle. (ii) The FT analysis revealed a change in the I–P region shape, indicating that events beyond PSI are affected. These events include a lesser density of PSI itself and the compromised ability of the end acceptors of electrons (ferredoxine, NADP + ) and RuBP to manage effectively the ﬂux of electrons. This behaviour may create an imbalance between electrons sent by the electron transport chain and those reaching the acceptors beyond PSI. Free electrons (those coming from PSI, but that do not reach the end acceptors) can activate the oxygen from fundamental to excited status, with production of ROS (Reactive Oxygen Species), thus inducing photo-oxidation processes of the cellular content. (iii) In many cases a temporarily enhanced efﬁciency of electron trapping and transport (expressed by the parameters FV/FM, ET/TR, PIABS, pQ) in PSII system has been observed. That efﬁciency has been connected to the triggering of repair processes, but when it is connected to a reduced end acceptor capacity in combination with reduced Calvin cycle energy demand lead to over-excitation of the photosynthetic apparatus and initiates response towards visible foliar injury. (iv) The behaviour of F0 can help us distinguish between different response strategies. The increase of F0 observed in some ozone-treated plant species is considered an expression of irreversible damage in PSII, whereas lowered values of this parameter may indicate the activation of PSII in the cells surrounding the damaged one, as part of a compensative process. Future directions for the research in this ﬁeld concern: (i) the possibility to combine ﬂuorescence parameters with carbon assimilation and growth to support the study on critical levels and (ii) the analysis of the events concerning the activity of PSI and the events leading to the ﬁxation of CO2, by using innovative technologies
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Chlorophyll a fluorescence; OKJIP transient; Open top chambers; Ozone stress; Performance index; Quantum yield efficiency; Reaction centres; Visible foliar symptoms

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential

Leaf morphology and macronutrients in broadleaved trees in central Italy - Bussotti, Filippo; Borghini, Francesca; Celesti, Carlo; Leonzio, Claudio; Bruschi, Piero (Trees, 2000)
As part of an intensive monitoring programme (MON.I.TO, Intensive Monitoring of Forests in Tuscany), a 3-year survey was carried out, which included three tree species (beech, Fagus sylvatica L.; Turkey oak, Quercus cerris L.; holm-oak, Quercus ilex L.) located at six different sites. Leaves were sampled annually and analysed for nutrient concentrations (nitrogen, sulphur, phosphorus, magnesium, calcium, potassium and sodium) and morphological parameters (leaf area, dry weight, leaf mass per area, leaf thickness and leaf density). Results indicated considerable interannual variation of all the parameters. Differences between sampling sites indicated that, of all parameters measured, leaf mass per area could explain best the differences in field performance under conditions of stress. In fact, leaf mass per area was greater in the drier sites or when sea salt deposition occurred. Nevertheless, the variation of leaf mass per area over the 3 years did not reflect the differences in rainfall. Higher leaf mass per area was accompanied by lower concentrations of phosphorus and nitrogen, which could be a dilution effect due to an increase of structural carbon compounds in sclerophyllous leaves, as revealed by the total foliar content of these elements. Leaf mass per area as a measure of sclerophylly reached very high values among mesophile vegetation. Long-range transport of sea salt from coastal areas to mountain areas was mirrored in sodium concentrations of leaves.
Keywords: Fagus sylvatica; macronutrients; Quercus cerris; Quercus ilex; sclerophylly

Leaf morphology and macronutrients in broadleaved trees in central Italy - Bussotti, Filippo; Borghini, Francesca; Celesti, Carlo; Leonzio, Claudio; Bruschi, Piero (Trees, 2000)
As part of an intensive monitoring programme (MON.I.TO, Intensive Monitoring of Forests in Tuscany), a 3-year survey was carried out, which included three tree species (beech, Fagus sylvatica L.; Turkey oak, Quercus cerris L.; holm-oak, Quercus ilex L.) located at six different sites. Leaves were sampled annually and analysed for nutrient concentrations (nitrogen, sulphur, phosphorus, magnesium, calcium, potassium and sodium) and morphological parameters (leaf area, dry weight, leaf mass per area, leaf thickness and leaf density). Results indicated considerable interannual variation of all the parameters. Differences between sampling sites indicated that, of all parameters measured, leaf mass per area could explain best the differences in field performance under conditions of stress. In fact, leaf mass per area was greater in the drier sites or when sea salt deposition occurred. Nevertheless, the variation of leaf mass per area over the 3 years did not reflect the differences in rainfall. Higher leaf mass per area was accompanied by lower concentrations of phosphorus and nitrogen, which could be a dilution effect due to an increase of structural carbon compounds in sclerophyllous leaves, as revealed by the total foliar content of these elements. Leaf mass per area as a measure of sclerophylly reached very high values among mesophile vegetation. Long-range transport of sea salt from coastal areas to mountain areas was mirrored in sodium concentrations of leaves.
Keywords: Fagus sylvatica; macronutrients; Quercus cerris; Quercus ilex; sclerophylly

European and Mediterranean oaks (Quercus L.; Fagaceae): SEM characterization of the micromorphology of the abaxial leaf surface - Bussotti, Filippo; Grossoni, Paolo (Botanical Journal of the Linnean Society, 1997)
This paper examines micromorphological characteristics (trichomes, waxes, stomata) of the abaxial leaf surface of European and Mediterranean oaks. Observations were performed In-scanning electron microscopy, and the purpose of the investigation was to ascertain whether it is possible to distinguish the different species taxonomically using these features. Several species, as well as some subspecific entities and taxa considered doubtful, were taken into consideration. Subgenera appear to be well-defined: e.g. the subgenus Quercus is characterized by waxes arranged in vertical scales, the subgenera Cenis and Sclerophyllodris by smooth waxes. They differ because the former has markedly elliptical stomata, while the latter two have roundish stomata. The different species are also fairly easy to distinguish, and this fact confirms the taxonomical validity of the parameters we have taken into consideration. In some cases subspecific entities and doublful species do not diflcr at all from the related species, but in others they present such marked variations that it is difficult even to classify them with certainty. The most critical taxonomic groups (i.e. those which include a number of specific and subspecific entities often too difficult to distinguish from each other) are the series Quercus robur – Quercus petraea,– Quercus pubescens and the Quercus faginea,– Quercus Insitanica Quercus canariensis group.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: stomata; taxonomy; Trichomes; waxes

European and Mediterranean oaks (Quercus L.; Fagaceae): SEM characterization of the micromorphology of the abaxial leaf surface - Bussotti, Filippo; Grossoni, Paolo (Botanical Journal of the Linnean Society, 1997)
This paper examines micromorphological characteristics (trichomes, waxes, stomata) of the abaxial leaf surface of European and Mediterranean oaks. Observations were performed In-scanning electron microscopy, and the purpose of the investigation was to ascertain whether it is possible to distinguish the different species taxonomically using these features. Several species, as well as some subspecific entities and taxa considered doubtful, were taken into consideration. Subgenera appear to be well-defined: e.g. the subgenus Quercus is characterized by waxes arranged in vertical scales, the subgenera Cenis and Sclerophyllodris by smooth waxes. They differ because the former has markedly elliptical stomata, while the latter two have roundish stomata. The different species are also fairly easy to distinguish, and this fact confirms the taxonomical validity of the parameters we have taken into consideration. In some cases subspecific entities and doublful species do not diflcr at all from the related species, but in others they present such marked variations that it is difficult even to classify them with certainty. The most critical taxonomic groups (i.e. those which include a number of specific and subspecific entities often too difficult to distinguish from each other) are the series Quercus robur – Quercus petraea,– Quercus pubescens and the Quercus faginea,– Quercus Insitanica Quercus canariensis group.
Keywords: stomata; taxonomy; Trichomes; waxes